Why should we screen for perinatal depression? Ten reasons to do it - Pereira, AT (2014)
In this paper we review some of the best available evidence to argue that screening for perinatal depression should be systematically conducted since pregnancy. Our view is organized in ten topics: (1) perinatal depression high prevalence; (2) its potential negative consequences, including maternal, conjugal, foetal, infantile, and child effects; (3) its under-detection and treatment; (4) its stigma; (5) the professionals and women misconceptions related to perinatal depression; (6) the availability of valid and short self-report screening instruments for perinatal depression and (7) their acceptability; (8) the increase in recognition, diagnosis, and treatment rates in comparison with routine practice; (9) the opportunity, given the large number of contacts that women have with health professionals in the perinatal period; and (10) perinatal depression screening potential cost-effectiveness.